2011
DOI: 10.1371/journal.pbio.1001216
|View full text |Cite
|
Sign up to set email alerts
|

Jamb and Jamc Are Essential for Vertebrate Myocyte Fusion

Abstract: Jamb and Jamc are an essential cell surface receptor pair that interact to drive fusion between muscle precursor cells during zebrafish development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 64 publications
13
93
0
Order By: Relevance
“…Linkage groups as well as chromosomes found were homologous groups as described in comparative mapping studies in seabass but also in the gilt-head sea bream compared with the five model fish species (29,75). Examples of putative paralogs involved in developmental processes, found in the present study, are orthodenticle 2 (otx2) (59), nodal (13a), the cell surface receptors junctional adhesion molecule b-like (jamb) (66), diencephalon/ mesencephalon homeobox 1, and orthopedia (otp). The latter three genes were expressed especially during organogenesis of seabass embryos.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Linkage groups as well as chromosomes found were homologous groups as described in comparative mapping studies in seabass but also in the gilt-head sea bream compared with the five model fish species (29,75). Examples of putative paralogs involved in developmental processes, found in the present study, are orthodenticle 2 (otx2) (59), nodal (13a), the cell surface receptors junctional adhesion molecule b-like (jamb) (66), diencephalon/ mesencephalon homeobox 1, and orthopedia (otp). The latter three genes were expressed especially during organogenesis of seabass embryos.…”
Section: Discussionsupporting
confidence: 71%
“…It has been shown that both paralogs of diencephalon/mesencephalon homeobox play an important role in brain development of zebrafish embryos (91) and that both paralogs of otp are essential for the development of a subset of dopaminergic neurons (20). Jamb on the other hand has been shown to play a pivotal role along with jamc during somitogenesis in fusion of myocyte precursors (66). For further downstream analysis only transcripts significantly differentially expressed in at least one of the studied stages were used.…”
Section: Discussionmentioning
confidence: 99%
“…Morpholino-dependent knockdown was, however, inefficient and it may be that a fusion defect would require a greater level of depletion. In contrast, JAM-B and -C, two different Ig superfamily counter-receptors, were essential for myoblast fusion in zebrafish (Powell and Wright 2011). Studies with mice carrying individual mutations in the members of the Kirrel, Nephrin, and JAM families have not been studied specifically for muscle development or myoblast fusion, but most mutants survive long enough that it is not possible for a complete block to myoblast fusion to have occurred in these animals (Donoviel et al 2001;Putaala et al 2001;Gliki et al 2004;Sakaguchi et al 2006;Prince et al 2013;Yesildag et al 2015).…”
Section: Cell -Cell Contact and Skeletal Myogenesismentioning
confidence: 99%
“…A previously validated translation-inhibiting antisense morpholino (MO) was designed against zebrafish Jam2a (Powell and Wright 2011). One hundred embryos were injected with 2 ng MO, 100 embryos were injected with 100 pg of mRNA, and 100 embryos were injected with both 2 ng MO and 100 pg mRNA; 100 uninjected embryos were used as a control.…”
Section: Morpholino Rescuementioning
confidence: 99%